The Role of Financial Planning in Mediating the Impact of Financial Literacy on the Financial Well-Being of Millennials in Jakarta - Iqbal Mardhani, Muhammad; Rahmanto, Basuki Toto (CV. Publikasi Indonesia, 2026)
Financial welfare is an important issue for the millennial generation, especially in DKI Jakarta which has high economic dynamics and consumptive lifestyles. Financial literacy is needed to improve an individual's ability to manage finances, but without good planning, this knowledge does not necessarily have an impact on well-being. This research aims to analyze the influence of financial literacy on financial well-being with financial planning as a mediating variable in the millennial generation in DKI Jakarta. The study used a quantitative approach with an explanatory design. Data was obtained through a survey of 400 respondents using a purposive sampling technique using a Likert scale questionnaire. Data analysis was carried out using the SEM-PLS method. The results showed that financial literacy had a positive and significant effect on financial well-being (β = 0.236) and had a strong effect on financial planning (β = 0.889). Financial planning also has a positive and significant effect on financial well-being (β = 0.708). In addition, financial planning is able to partially mediate the influence of financial literacy on financial well-being with a greater indirect influence (β = 0.630). The financial well-being of the millennial generation is not only influenced by financial literacy, but also by the ability to implement structured and effective financial planning.